Factors Influencing Preparation for Integration of Primary Health Services in the Work Area of ​​the Asahan District Health Office - Lumban Gaol, Nourma Yenthi; Balqis Wasliati; Ika Nur Saputri (JURNAL KESMAS DAN GIZI (JKG), 2025)
The Government of Indonesia is currently undertaking a health systemtransformation through the Integration of Primary Health Care Services (ILP) to improve access, quality, and efficiency of services at the Puskesmas (community health center) level. However, the readiness for ILP implementation still faces various challenges, particularly in the working area of the Asahan District Health Office. This study aims to analyze the factors influencing the readiness for ILP implementation in three Puskesmas in Asahan Regency: Puskesmas Rawang Pasar IV, Puskesmas Meranti, and Puskesmas Binjai Serbangan. This research used a quantitative approach with a cross-sectional design. A total of 105 respondents were selected using a stratified random sampling technique. Data were collected through questionnaires and analyzed using chi-square tests and logistic regression. Bivariate analysis showed that human resources (p=0.016).and digital information systems (p=0.004) significantly influenced ILP readiness. Meanwhile, facilities and medical equipment (p=1.000) and stakeholder involvement (p=0.495) did not have a significant effect. Multivariate analysis revealed that the digital information system was the most dominant factor (Exp(B)=6.893), followed by human resources (Exp(B)=3.888). Human resources and digital information systems significantly influence ILP readiness. Therefore, enhancing the competence of health personnel and strengthening digital information systems are strategic priorities to support the successful implementation of ILP at the Puskesmas level.